2014
DOI: 10.1007/s10522-014-9531-2
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding proteins as molecular links between cancer and neurodegeneration

Abstract: For many years, epidemiological studies have suggested an association between cancer and neurodegenerative disorders-two disease processes that seemingly have little in common. Although these two disease processes share disruptions in a wide range of cellular pathways, including cell survival, cell death and the cell cycle, the end result is very divergent: uncontrolled cell survival and proliferation in cancer and progressive neuronal cell death in neurodegeneration. Despite the clinical data connecting these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 263 publications
(272 reference statements)
1
32
0
Order By: Relevance
“…From the point of view of the neurodegeneration, cell cycle dysregulation could have some significance for neuronal pathology as it has been reported that neurons undergoing degeneration re-enter the cell cycle, leading to apoptosis rather than cellular division, as recently reviewed by Campos-Melo et al. ( 68 ). In addition, the finding that TDP-43 can affect STAG2 splicing also offers a new connection with recent reports that depict its possible role in tumorigenesis, since recent cancer genomics analyses have reported a rather large number of somatic mutations at the level of the core cohesin factors ( SMC1A, SMC3, RAD21 and STAG1/2 ) in a particular subset of human tumours including Ewing sarcoma, an aggressive bone tumour ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the point of view of the neurodegeneration, cell cycle dysregulation could have some significance for neuronal pathology as it has been reported that neurons undergoing degeneration re-enter the cell cycle, leading to apoptosis rather than cellular division, as recently reviewed by Campos-Melo et al. ( 68 ). In addition, the finding that TDP-43 can affect STAG2 splicing also offers a new connection with recent reports that depict its possible role in tumorigenesis, since recent cancer genomics analyses have reported a rather large number of somatic mutations at the level of the core cohesin factors ( SMC1A, SMC3, RAD21 and STAG1/2 ) in a particular subset of human tumours including Ewing sarcoma, an aggressive bone tumour ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RBPs have been discovered to be a molecular link between human disease processes that seem to be very different from each other, such as cancer and neurodegeneration (Campos‐Melo et al . ).…”
mentioning
confidence: 97%
“…On the other hand, genes that are mainly involved in DNA/RNA metabolism are more closely associated with ALS phenotype (Hardy and Rogaeva 2014). Furthermore, RBPs have been discovered to be a molecular link between human disease processes that seem to be very different from each other, such as cancer and neurodegeneration (Campos-Melo et al 2014).…”
mentioning
confidence: 99%
“…The unique functions also include pre-mRNA splicing and DNA repair and recombination (11). Notably, chromosomal rearrangements result in the 5' regions of FET genes being fused with different transcription factor genes in sarcomas or other types of cancer (12)(13)(14). FUS/TLS was identified as a fusion gene with DNA damage inducible transcript 3 (CHOP) (also known as GADD153, DDIT3) in human myxoid liposarcoma with chromosomal translocation t(12; 16)(q13; p11) (15).…”
Section: Elevated Fus/tls Expression Is Negatively Associated With E-mentioning
confidence: 99%